Protecting newborns from pertussis: The role of partner vaccination in the era of maternal immunization. (September 2017) - Krishnaswamy, Sushena; Wallace, Euan M.; Cheng, Allen C.; Buttery, Jim; Giles, Michelle L.
Abstract: Objective(s): While antenatal vaccination is the most effective strategy to reduce newborn pertussis infection and its associated morbidity and mortality, uptake has consistently been reported to be suboptimal. "Cocooning" or vaccination of the close contacts of newborns therefore remains an important strategy for protecting newborns when maternal vaccination has not occurred or with insufficient time for antibody transfer. This study assesses the uptake of pertussis vaccination by parents and close contacts of newborns providing insight into the vulnerability of newborns to pertussis upon discharge from hospital to their primary carers. Study design: The study was conducted at three public and two private hospitals in Melbourne, Australia. A survey was administered to 689 women and/or their partners admitted on maternity wards of participating hospitals after delivery of a healthy newborn between August and December 2016. The main outcomes measured were reported vaccination rates and factors associated with uptake of pertussis vaccination. Kappa statistic and logistic regression were used to determine factors associated with vaccination. Results: 70% of women and 66% of partners reported pertussis vaccination according to national recommendations. Significantly 22% of newborns were discharged to a household where neither parent reported vaccination. Compared to when maternal vaccination did occur, in families where it didn't there were low rates of vaccination of partners (83% vs 26%) and other carers, particularly carers usually resident overseas (76% vs 18.5%). Conclusion(s): While the majority of mothers and partners reported pertussis vaccination in accordance with recommended guidelines, concerningly nearly a quarter of newborns were discharged to a home where neither parent was vaccinated. When maternal vaccination did not occur, rates of vaccination of the other close contacts was poor. Educating women to encourage vaccination of partners and carers particularly those coming from overseas, prior to their arrival is an important consideration when maternal immunization does not occur. Cocooning remains an important approach to protect newborns of mothers vaccinated late or not vaccinated in pregnancy.